2014
DOI: 10.1055/s-0034-1365016
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation can significantly reduce toilet use after colonoscopy: a double-blind randomized controlled trial

Abstract: Insufflation with CO2 can significantly reduce abdominal discomfort and toilet use after colonoscopy. Use of this technique may help reduce patient burden and allow more efficient use of space in the endoscopy unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Forty RCT with 13 734 patients were included from 1060 articles searched through databases and other sources (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty RCT with 13 734 patients were included from 1060 articles searched through databases and other sources (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐three studies focused on the analysis regarding cecal intubation time. According to our analysis, we did not get any significant results on cecal intubation time.…”
Section: Resultsmentioning
confidence: 99%
“…This is because CO 2 is absorbed by the bowel lumen rapidly. Hsu et al 10 demonstrated a reduction in the frequency and total duration of toilet use in the first 2 h after colonoscopy with CO 2 insufflation. This indicated that absorption of CO 2 is more rapid than that of room air, and the majority of CO 2 volume is absorbed in the early stage after colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7]12 However, there are limited reports about CO 2 insufflation during colonoscopy in deeply sedated patients. 8,10,[13][14][15] The aims of the present study were to investigate the subjective and objective efficacy of CO 2 insufflation in reducing postprocedural abdominal discomfort, evaluation of patients' satisfaction after colonoscopy, and assessment the safety of CO 2 insufflation during colonoscopy in patients deeply sedated with propofol.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several clinical reports of CO 2 insufflation for colonoscopy have been reported . A meta‐analysis investigating 21 RCT comprising 3607 colonoscopy patients reported that CO 2 insufflation for colonoscopy could have clinical advantages regarding abdominal pain during and after the procedure .…”
Section: Introductionmentioning
confidence: 99%